Improving the information culture of a future geography teacher based on geoinformation technologies - FAZLIDDIN, KHAZRATOV (The journal of contemporary issues in business and government, 2021)
This article explores the knowledge and skills required to improve the skills of geography teachers today using geographic information systems. In addition, the article provides instructions for geography teachers on the use of information technology in teaching GIS. The article describes the problems of modern teaching of the course "Geographic Information Systems" and ways to solve them.